Electrical characterization of Si nanoparticles embedded in SiO2 thin films - Do Kim, Yang; Kim, Eun Kyu; Lee, Soojin; Cho, Woon Jo (KOREAN PHYSICAL SOC, 2006)
A floating gated quantum dot memory using threshold shifting from charges stored in nanoparticles of silicon is expected to be promising candidate for future nonvolatile memory devices. Silicon nanoparticles of 1 similar to 5 nm in diameter embedded in SiO2 thin films were made by using an ultrasound induced solution method. SiO2 layers were deposited by RF magnetron sputtering in pure Ar gas. The substrate temperatures was changed from room temperature to 200 degrees C under the same deposition conditions. From the capacitance-valtage measurements of metal-oxide-semiconductor capacitors fabricated with the Si nanopaticles in the SiO2 layer, the flat-band voltages changed by about 4.8 V due to charging and discharging to the nanoparticles.